PENGARUH IMPLEMENTASI MODEL ROLE-PLAYING GUNA MENINGKATKAN HASIL BELAJAR SISWA - Abdul Rauf, (UNISAN JURNAL, 2024)
This examination plans to portray the utilization of the Pretending Strategy in expanding comprehension of Islamic social history subjects in the homeroom. The kind of examination utilized is field research. This examination is a subjective engaging review. The information source in this examination was acquired from the class XI educator. Information assortment strategies in this exploration included perception, meetings and documentation techniques. The information examination strategy utilized is subjective unmistakable investigation which comprises of information decrease, information show and information confirmation. The examination results show that the use of the Pretending strategy can increment understudy learning exercises utilizing Pretending. Understudies feel cheerful in learning and don't get exhausted rapidly so exceptionally that therefore understudy movement increments. The use of the Roe Playing strategy applies the pretend technique to rhyme material. This implies that a learning execution plan is ready as per the pretending steps, making understudy worksheets, as well as getting ready understudy exercises and assessment instruments to gauge's comprehension understudies might interpret the material utilized toward the finish of each growing experience.